2020
DOI: 10.7759/cureus.7835
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) in Cancer Patients

Abstract: The Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become the most talked-about clinical entity in early 2020. As an infection that spreads easily and has a significant mortality rate, it has caused global panic rarely seen before. Many of the measures taken by governments worldwide will have longlasting impacts on the wellbeing of the population at large. It has been widely reported that the most vulnerable patients have been most negatively af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…In fact, cancer patients are prone to engender psychiatric diseases such as anxiety and depression. Adding to this, lockdown and isolation imposed by the emerging of COVID-19 have created a sense of collective hysteria, and delaying treatment could be an important factor of increased stress ( Cancarevic et al, 2020 ). In other words, constant fear and uncertainty caused by the pandemic could harm cancer patients’ quality of life ( Chakraborty and Pandey, 2020 ), and this was illustrated by more than one survey in cancer population.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, cancer patients are prone to engender psychiatric diseases such as anxiety and depression. Adding to this, lockdown and isolation imposed by the emerging of COVID-19 have created a sense of collective hysteria, and delaying treatment could be an important factor of increased stress ( Cancarevic et al, 2020 ). In other words, constant fear and uncertainty caused by the pandemic could harm cancer patients’ quality of life ( Chakraborty and Pandey, 2020 ), and this was illustrated by more than one survey in cancer population.…”
Section: Resultsmentioning
confidence: 99%
“…With sudden, unexpected, change in guidance comes concern over the psychological impact that the current COVID19 pandemic will have on these high-risk patient groups, where an increased risk of anxiety, depression and post-traumatic stress disorder (PTSD) is already well documented. 7 , 8 Previous viral outbreaks, such as from severe acute respiratory syndrome (SARS), have reported that the psychological impact of quarantine (i.e. an imposed quarantine when a person has the virus) can vary from short-term effects such as irritability, fear, confusion, anxiety and depression, to extremes of consequence, including PTSD and suicide.…”
mentioning
confidence: 99%
“…Both loneliness and social distancing also increases risk of mortality in cancer patients, while feelings of uncertainty increased emotional distress 12,13 . Multiple sources have suggested the need for more frequent contact, via telephone or video consultation, with healthcare professionals to increase social support 14,15 . Issues regarding trust, isolation and worries about abandonment should also be proactively addressed 16 .…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%